Effectiveness of Managing Emotion Techniques in Group Counseling to Prevent Aggressiveness of High School Students - Veno Dwi Krisnanda (Sosio e-Kons, 2019)
This study used experimental research with a pretest-group control design design. The subject of this study were 14 students of class XI who had aggressiveness in the high category. There are two types of instruments used in this study, namely the instruments for the treatment and instrument of data collection. Based on the results of the study based on the independent Gain Score statistical analysis of the sample t-test with the data value The level of aggressive behavior of the experimental group was lower than the control group Conclusion was that anger management techniques in group counseling had an effect on student aggressive behavior